How to design and implement an outpatient antimicrobial stewardship programme - Emily N Drwiega; Nicole Griffith; Fischer Herald; Melissa E Badowski (BioExcel Publishing Ltd, 2023)
Antimicrobial stewardship programmes in the outpatient setting have recently become an area of focus in an effort to improve antimicrobial prescribing. The Centers for Disease Control and Prevention and The Joint Commission have recently addressed this concern and provided a framework for the implementation of an outpatient stewardship programme. This manuscript offers detailed guidance on how to design and implement an outpatient antimicrobial stewardship programme and reviews the literature on current strategies. Challenges related to initiating and maintaining outpatient stewardship efforts are also discussed. This article is part of the Antibiotic stewardship Special Issue: https://www.drugsincontext.com/special_issues/antimicrobial-stewardship-a-focus-on-the-need-for-moderation